Reporting Guidelines for Music-based Interventions: an update and validation study - Robb, Sheri L.; Springs, Stacey; Edwards, Emmeline; Golden, Tasha L.; Johnson, Julene K.; Burns, Debra S.; Belgrave, Melita; Bradt, Joke; Gold, Christian; Habibi, Assal; Iversen, John R.; Lense, Miriam; et al. (Frontiers in Psychology, 2025)
BackgroundDetailed intervention reporting is essential to interpretation, replication, and translation of music-based interventions (MBIs). The 2011 Reporting Guidelines for Music-Based Interventions were developed to improve transparency and reporting quality of published research; however, problems with reporting quality persist. This represents a significant barrier to advances in MBI scientific research and translation of findings to practice.ObjectiveTo update and validate the 2011 reporting guidelines using a rigorous Delphi approach that involved an interdisciplinary group of MBI researchers; and to develop an explanation and elaboration guidance statement to support dissemination and usage.MethodsWe followed the methodological framework for developing reporting guidelines recommended by the EQUATOR Network and guidance recommendations for developing health research reporting guidelines. Our three-stage process included: (1) an initial field scan, (2) a consensus process using Delphi surveys (two rounds) and Expert Panel meetings, and (3) development and dissemination of an explanation and elaboration document.ResultsFirst-Round survey findings revealed that the original checklist items were capturing content that investigators deemed essential to MBI reporting; however, it also revealed problems with item wording and terminology. Subsequent Expert Panel meetings and the Second-Round survey centered on reaching consensus for item language. The revised RG-MBI checklist has a total of 12-items that pertain to eight different components of MBI interventions including name, theory/scientific rationale, content, interventionist, individual/group, setting, delivery schedule, and treatment fidelity.ConclusionWe recommend that authors, journal editors, and reviewers use the RG-MBI guidelines, in conjunction with methods-based guidelines (e.g., CONSORT) to accelerate and improve the scientific rigor of MBI research.